Enhancing writing skills - Elufiede, Oluwakemi; Murray, Tina; Boden, Carrie J. (Adult learning in professional, organizational, and community settings., 2016)
Enhancing Writing Skills includes conference presentation papers from the Carnegie Writers, Inc. 1st Annual Conference. The anthology provides published and aspiring writers resources for sustaining, enhancing and evaluating their writing skills. The chapter themes focus on genre-based writing, creativity in writing, mechanics of writing, academic writing, and writing as a business. Enhancing writing skills is beneficial to diverse writers as it impacts the community, working, and educational environments. Anthology goals and ojbjectives: - Enable writers to learn from other writers for the development of networking relationships and professional development. - Assist writers with techniques on sustaining their writing talents in their chosen genre or various genres. - Provide meaningful publishing resources related to non-traditional and traditional publication venues. - Enhance writers understanding for marketing strategies in the 21st century.